Tuning uracil derivatives for the AIE-based detection of pyrene at a nano-molar level: single-crystal X-ray structure and DFT support. (1st September 2020) - Banerjee, Mahuya; Ghosh, Milan; Ta, Sabyasachi; Ghosh, Subhasis; Das, Debasis
Abstract : Single crystal X-ray structurally characterized azo-uracil derivative (L) is explored for the selective detection of pyrene via aggregation-induced emission (AIE) with 99-fold fluorescence enhancement. Abstract : Single crystal X-ray structurally characterized azo-uracil derivative (L) is explored for the selective detection of pyrene via aggregation-induced emission (AIE) with 99-fold fluorescence enhancement. In the presence of pyrene, non-fluorescent L emits green light and allows pyrene detection to as low as 3.6 × 10 −9 M. Three model probes (L1, L2 and L3) were employed to support the proposed sensing mechanism. Further, silica-immobilized L efficiently removes pyrene from its reservoir.